PERFORMANCE CULTURE IN INSTRUMENTAL PERFORMANCE - Botirova Khilola Tursunbaevna; Samandarov Nuriddin Maxammatjon ugli (Journals Park Publishing, 2022)
This in the article executive art, culture concepts illuminate mentioned, this with a in a row from the performer executive in practice dynamics on performance importance showing mentioned.
Keywords: Music culture; terminology; performer